Synkretyzm antroponimii Podlasia - Abramowicz, Zofia (Poznańskie Spotkania Językoznawcze, 2014)
<span style="color: black; line-height: 150%; font-family: 'Times New Roman',serif; font-size: 12pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The wise policy of stimulating the social processes in the Grand Duchy of Lithuania caused strong integration trends in area of the ethnic diversification of the population. A phenomenon of tolerance enabled inhabitants of Podlasie the coexistence and the symbiosis, gave a base to create the syncretic culture of the borderland. It was manifested in onomastics. On the one hand, the anthroponymy of Podlasie is reflecting the coexistence of many languages and cultures, on the other − forming some identifying formulas common for all ethnic and religious groups. The synergy and overlapping different patterns in onomastics showed results in hybrid formations and some structures, typical only for given region, what was the most reflected in an abridged names and surnames forms of Podlasie inhabitants.